2013
DOI: 10.2118/154467-pa
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Under Uncertainty: Applying the Least-Squares Monte Carlo Method in Surfactant-Flooding Implementation

Abstract: This study introduces a decision-making evaluation method for flexibility in surfactant flooding. The method aims to capture the effects of uncertainty in the time series for both technical and economic parameters and produce a near-optimal policy with respect to these uncertainties as they vary with time. The evaluation method used was the least-squares Monte Carlo (LSM) method, which is best-suited for evaluating flexibility in project implementation. The decision analyzed was that of finding the best time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It was demonstrated that the optimal policy obtained was reliable and that heterogeneity and different well-placement patterns affect the value of flexibility and optimal policy for different reservoir models [48].…”
Section: Monte Carlo Methods In Surfactant Flooding Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the optimal policy obtained was reliable and that heterogeneity and different well-placement patterns affect the value of flexibility and optimal policy for different reservoir models [48].…”
Section: Monte Carlo Methods In Surfactant Flooding Implementationmentioning
confidence: 99%
“…A decision-making evaluation method for flexibility in surfactant flooding has been presented [48]. The method aims to the capture the effects of uncertainty in the time series for both technical and economic parameters and produce a near optimal policy with respect to these uncertainties as they vary with time.…”
Section: Monte Carlo Methods In Surfactant Flooding Implementationmentioning
confidence: 99%